2018
DOI: 10.4103/aer.aer_13_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of arterial oxygenation and acid-base balance with the use of transnasal humidified rapid-insufflation ventilatory exchange versus tidal volume breathing with continuous positive airway pressure for preoxygenation and apneic ventilation

Abstract: Background:Preoxygenation and apneic ventilation prolong apnea time without desaturation.Aims:The primary objective of this study is to compare arterial oxygenation during the periods of apnea following preoxygenation and apneic ventilation with tidal volume breathing for 3 min with continuous positive airway pressure (CPAP) versus with transnasal humidified rapid-insufflation ventilatory exchange (THRIVE).Settings and Designs:This prospective randomized study was conducted in 20 adult patients at a tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 18 publications
(17 reference statements)
1
1
0
Order By: Relevance
“…HFNO produced a higher PaO2 after pre-oxygenation and safe PaO2 during intubation. Another preliminary study [ 22 ] found similar results. No previous study has simultaneously assessed facemask and HFNO for optimizing both preoxygenation and apnoeic oxygenation in a large multinational study.…”
Section: Discussionsupporting
confidence: 71%
“…HFNO produced a higher PaO2 after pre-oxygenation and safe PaO2 during intubation. Another preliminary study [ 22 ] found similar results. No previous study has simultaneously assessed facemask and HFNO for optimizing both preoxygenation and apnoeic oxygenation in a large multinational study.…”
Section: Discussionsupporting
confidence: 71%
“…Both treatments were equally effective in prolonging SAP without desaturation for up to 12 minutes. The CPAP group had an added advantage of lower PaCO 2 with less acidosis 5 . The use of high-flow nasal O 2 during pre-oxygenation and then continued during apnea can also prevent hypoxia before and during intubation attempts by extending SAP 6 .…”
Section: Airway Managementmentioning
confidence: 99%